Prevalence of hyperuricemia in Chitwan District of Nepal - Kumar, S; Singh, AR; Takhelmayum, R; Shrestha, P; Sinha, JN (Journal of College of Medical Sciences-Nepal, 2010)
The prevalence of hyperuricemia has been increasing in both developed and developing countries. The purpose of present study was to know the prevalence of hyperuricemia in the population of Chitwan district as well as to compare the prevalence of hyperuricemia between Mongolian and non-Mongolian races of Chitwan district, who had attended the College of Medical Sciences and Teaching Hospital, Bharatpur, Nepal during the period of January 1999 to December 2003. In this study 3794 subjects were investigated for serum uric acid level (SUA). Hyperuricemia is defined as SUA more than 7mg/dl for males and menopausal women and 6mg/dl for pre-menopausal females. SUA was estimated by Caraway method in digital colorimeter. Overall prevalence was 21.42%; the condition was more common in men than women (26.78% vs. 16.82%; p<0.001). The prevalence was higher in Mongolian than non Mongolian both in males and females (24.50 % Vs 21.06%; p>0.05). Key words: Hyperuricemia; SUA; digital colorimeter DOI: 10.3126/jcmsn.v6i2.3612 Journal of college of Medical Sciences-Nepal, 2010, Vol.6, No-2, 18-23